Clinical Characteristics and Risk Factors for Infantile Hemangioma—A Case Control Study - Rasul, Sadykov (European Journal of Pediatric Surgery, 2014)
Objective To study the demographic and clinical features of infantile hemangioma in Uzbekistan; to learn in more detail the risk factors for developing this disease; and to identify clinical characteristics associated with complications, associated risks, and the need for systemic treatment.Material and Methods A case-control study of 1,832 prospectively enrolled children and 1,832 controls matched with hemangiomas for age, sex, region, and hospital attending the maxilla facial surgery and dermatology departments between 2008 and 2012 was conducted. The patient data were collected from archives of three large hospitals in Uzbekistan Demographic and clinical presentations were summarized and compared with data from previous studies of hemangiomas. Predictive clinical factors for complications and/or treatment and potential risk factors for infantile hemangiomas were analyzed by logistic regression.Results The clinical features of this study's patients were different from those of other race/ethnicity groups reported by previous studies with regard to the morphological subtypes, complications, and predictors for complications and/or surgical and medicament treatment. After adjustment, significant risk factors for hemangiomas included lower level of maternal education (odds ratio [OR], 0.61; 95% confidence interval [CI], 0.57–0.66), mother engaged in manual labor (OR, 1.29; 95% CI, 1.12–1.48), multiple gestation (OR, 1.20; 95% CI, 1.05–1.36), maternal medication use during the periconceptional period (OR, 2.08; 95% CI, 1.88–2.31), and a positive family history of hemangiomas (OR, 1.55; 95% CI, 1.40–1.72).Conclusion Besides yielding several new findings with respect to risk factors for hemangiomas, the current study also suggests that the Uzbekistan clinical features of hemangiomas are somewhat different epidemiologically from those in the West.
Keywords: hemangioma; vascular anomalies; surgery; demography